THE ROLE OF VOCABULARY MASTERY AND LEARNING INTEREST IN SPEAKING PROFICIENCY OF INDONESIAN EFL LEARNERS - Enggar Dyah Puntadewi; Engliana Engliana (Universitas Indraprasta PGRI, 2018)
Abstract: The purpose of this study was to determine whether there is any influence of vocabulary mastery and students’ learning interest in learning on English speaking skills of State Junior High School students in Bogor City - West Java. This research was conducted in several state junior high schools in the city of Bogor, including SMP Negeri 1 Bogor, SMP Negeri 2 Bogor, and SMP Negeri 5 Bogor. The population in this study were all students of class VII at State Junior High Schools in the City of Bogor - West Java. The research results obtained that EFL speaking skills required good vocabulary mastery and high learning interest. Samples were taken by simple random technique. Research data on Speaking Skills was carried out with the technique of giving oral tests on speaking assignments. Data about vocabulary mastery is done by giving written test technique, while data about learning interest is collected using questionnaire-shaped instruments. Data analysis was performed by multiple linear regression analysis. Based on the results of the hypothesis and data analysis, the following conclusions are made: 1) There is a significant influence in the mastery of English vocabulary and interest in learning together on English speaking skills of state junior high school students in Bogor, West Java Province. This is evidenced by the acquisition of Sig. 0,000 <0.05 and Fh = 13,058. 2) There is a significant influence of vocabulary mastery on English speaking skills of State Junior High School students in the city of Bogor, West Java Province. This is evidenced by the acquisition of Sig. 0.007 <0.05 and th = 2.777. 3) There is a significant influence of learning interest on English speaking skills of State Junior High School students in the city of Bogor, West Java Province. This is evidenced by the acquisition of Sig. 0.001 <0.05 and th = 3.493.Keywords: vocabulary mastery; speaking skill; foreign language; learning interest